2018 ASEE Annual Conference &Amp; Exposition Proceedings
DOI: 10.18260/1-2--31217
|View full text |Cite
|
Sign up to set email alerts
|

Using Veterans' Technical Skills in an Engineering Laboratory

Abstract: where he is a member of the Electrical and Computer Engineering Department and IDoTeach, a pre-service STEM teacher preparation program. His work focuses on the transition from pre-college to university engineering programs, how exposure to engineering prior to matriculation affects the experiences of engineering students, and engineering in the K-12 classroom. He has worked as a high school science, mathematics, and engineering and technology teacher, as well as several years of electrical and mechanical engi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 2 publications
0
10
0
Order By: Relevance
“…As noted previously, five studies included in this review engaged with non-military participants [16], [21], [24], [29] or participants whose family members have served [11]. In developing a mechanical engineering course that introduces military technology to engineering students, Dalhberg and colleagues [29] found that both military and non-military students found the course to be beneficial to developing an understanding of mechanical engineering topics.…”
Section: Military Statusmentioning
confidence: 95%
See 3 more Smart Citations
“…As noted previously, five studies included in this review engaged with non-military participants [16], [21], [24], [29] or participants whose family members have served [11]. In developing a mechanical engineering course that introduces military technology to engineering students, Dalhberg and colleagues [29] found that both military and non-military students found the course to be beneficial to developing an understanding of mechanical engineering topics.…”
Section: Military Statusmentioning
confidence: 95%
“…This study suggests that introducing military technology in engineering courses can have a positive impact on military and non-military students and may be an effective way of creating inclusive environments for military students in engineering. Likewise, Salzman and colleagues [21] and Stringer and McFarland [16] found that when an undergraduate veteran with technical engineering expertise was placed in a leadership position in a lab-based class, both the veteran and the non-veteran students benefited from the veterans's knowledge and participation.…”
Section: Military Statusmentioning
confidence: 99%
See 2 more Smart Citations
“…Initial work has focused primarily on issues of practical importance for SVSM and for engineering programs seeking SVSM participation, including programmatic needs to identify military veterans, to develop faculty understandings of SVSM characteristics, to provide transitioning SVSM information about engineering careers, to establish processes for awarding academic credit for military training and experience, and to create veteran friendly campus climates [5]. Subsequent work has (1) explored specific ways in which the SVSM talents can be used in existing engineering courses [e.g., [41][42][43][44][45] and (2) disseminated information and assessments of innovative programs currently underway to support SVSM along ETETE career pathways [e.g. [46][47][48][49][50][51].…”
Section: Svsm Research In Higher Educationmentioning
confidence: 99%